Indicadores das condições nutricionais na região do Polonoroeste: III. Estudo clínico nutricional - Albuquerque, M.C.W. (1988)
This work is part of the clinical nutritional evaluation of the "Health Diagnostic in the Polonoroeste Survey, 1983". With the objective of evaluating the nutritional status of the population in the area of Polonoroeste a Nutritional Inquiry was done in 7 cities of the State of Mato Grosso. The inquiry included a study of alimentary habits, anthropometric studies and a clinical evaluation of the nutritional status of children between 3 and 72 months of age. We examined 585 children selected as proposed by the SANCHES & CARVALHEIRO sampling method modified by MEIRELLES and SANCHES and the clinical-nutritional evaluation was made according to JELLIEFE. Clinical evidence of proteic-energetic malnutrition was registered in 6.6% of the children, anemia in 9.7% and goiter in 2.7%. There was correlation of the anemia with intestinal parasitoses observed in the same sample by another team of the same project.